TEACHER ENGAGEMENT WITH ACADEMIC READING IN A POST-SERVICE TESOL COURSE - Kitchen, Margaret; Jeurissen, Maree; Gray, Susan; Courtney, Matthew (Universitas Pendidikan Indonesia, 2017)
Engaging school teachers with academic reading is challenging for all teacher trainers, yet if teachersâ€™ knowledge base is to be up-to-date the input of new research information is essential. Within the field of teacher professional development, few research studies focus primarily on teacher academic reading.Â On the Auckland New Zealand TESOL diploma course reported on here, academic readings are key. They theorise the weekly lecture topics and provide practical strategies that embed the theory. Three approaches to academic reading are used.Â These three approaches are the focus of the study reported here, exploring the attitudes of the 49 elementary and secondary school teachers over the two years of the part-time course. Quantitative questionnaire findings and relevant qualitative interview data which explicate the quantitative findings are reported on. The key finding was that, on average, the entire sample exhibited a large and statistically significant increase in engagement in academic reading over the two-year period. A majority of the teachers favoured the third approach to academic reading, being tightly structured, supportive reading groups rather than independent reading or reading presentation to a group. They valued the interdependence and reciprocity of the tightly structured reading groups.